Advancing the Real-World Evidence for Medical Devices through Coordinated Registry Networks. (14th November 2022) - Sedrakyan, Art; Marinac-Dabic, Danica; Campbell, Bruce; Aryal, Suvekshya; Baird, Courtney E; Goodney, Philip; Cronenwett, Jack L; Beck, Adam W; Paxton, Elizabeth W; Hu, Jim; Brindis, Ralph; Baskin, Kevin; et al.
Abstract : Objectives: Generating and using real-world evidence (RWE) is a pragmatic solution for evaluating health technologies. RWE is recognized by regulators, health technology assessors, clinicians, and manufacturers as a valid source of information to support their decision-making. Well-designed registries can provide RWE and become more powerful when linked with electronic health records and administrative databases in coordinated registry networks (CRNs). Our objective was to create a framework of maturity of CRNs and registries, so guiding their development and the prioritization of funding. Design, setting, and participants: We invited 52 stakeholders from diverse backgrounds including patient advocacy groups, academic, clinical, industry and regulatory experts to participate on a Delphi survey. Of those invited, 42 participated in the survey to provide feedback on the maturity framework for CRNs and registries. An expert panel reviewed the responses to refine the framework until the target consensus of 80% was reached. Two rounds of the Delphi were distributed via Qualtrics online platform from July to August 2020 and from October to November 2020. Main outcome measures: Consensus on the maturity framework for CRNs and registries consisted of seven domains (unique device identification, efficient data collection, data quality, product life cycle approach, governance and sustainability, quality improvement, and patient-reported outcomes), each presented with five levels of maturity. Results: Of 52 invited experts, 41 (79.9%) responded to round 1; all 41 responded to round 2; and consensus was reached for most domains. The expert panel resolved the disagreements and final consensus estimates ranged from 80.5% to 92.7% for seven domains. Conclusions: We have developed a robust framework to assess the maturity of any CRN (or registry) to provide reliable RWE. This framework will promote harmonization of approaches to RWE generation across different disciplines and health systems. The domains and their levels may evolve over time as new solutions become available.